2021
DOI: 10.1016/j.isci.2021.102263
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and physicochemical study of a biomass-derived CO2 sorbent 2,5-furan-bis(iminoguanidine)

Abstract: Summary In this study, the concept of biomass-based direct air capture is proposed, and the aminoguanidine CO 2 chemical sorbent 2,5-furan-bis(iminoguanidine) (FuBIG) was designed, synthesized, and elucidated for the physicochemical properties in the process of CO 2 capture and release. Results showed that the aqueous solution of FuBIG could readily capture CO 2 from ambient air and provided an insoluble tetrahydrated carbonate sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The GBIG compound was further examined and modified. For example, the synthesis and evaluation of a modified GBIG chemical sorbent, namely 2,5-furan-bis(iminoguanidine) (FuBIG), was investigated [40]. Firstly, the study reported the determination of two binding modes with nine hydrogen bonds between FuBIG, CO 2 (as CO 3 2− ), and H 2 O using single-crystal XRD analysis.…”
Section: Family Of Bis-iminoguanidine Carbonate Salts Used For Dac Ma...mentioning
confidence: 99%
“…The GBIG compound was further examined and modified. For example, the synthesis and evaluation of a modified GBIG chemical sorbent, namely 2,5-furan-bis(iminoguanidine) (FuBIG), was investigated [40]. Firstly, the study reported the determination of two binding modes with nine hydrogen bonds between FuBIG, CO 2 (as CO 3 2− ), and H 2 O using single-crystal XRD analysis.…”
Section: Family Of Bis-iminoguanidine Carbonate Salts Used For Dac Ma...mentioning
confidence: 99%